KERAGAMAN SERTA KELIMPAHAN KUMBANG TINJA DI PT CITRA PUTRA KEBUN ASRI KECAMATAN JORONG KABUPATEN TANAH LAUT - Bunga Resa Hartati; Abdi Fithria; Setia Budi Peran (Universitas Lambung Mangkurat, 2020)
The diversity and abundance of dung beetles is one indicator of degradation of a habitat. This research was conducted at PT Citra Putra Kebun Asri Jorong District Tanah laut Regency. The purpose of this study was to determine the abundance and diversity of fecal beetles. The research method used is purposive sampling method by using transect with length 1 km which conducted observation for 1 week. The method of dung beetle research is done by trapping the Baited Pitfall Trap which uses human waste as bait. Based on the results of this study the highest stool beetle diversity index (H ') was found in the location of wet tropical forests in Pangrango Gede National Park at 2.85 with a total of 86 individuals, while the lowest (H') diversity index was found in oil palm plantation 2 for 2,20259 with a total of 315 individuals. The highest abundance of fecal beetles was found in rubber plantation locations with a total of 1,031 and the lowest was in the wet tropical forest in the Pangrango Gede National Park of 0.91.Keywords: Diversity; Dung Beetles; Baited Pifalltra